Tutorial akademicki w naukach filologicznych na tle założeń interakcyjnego dyskursu glottodydaktycznego – krytyczna analiza różnic i podobieństw - Karpińska-Musiał, Beata (Neofilolog, 2017)
The article is a comparative study of a few chosen criteria of interactive discourse in glottodidactics, as formulated by Anna Seretny (2014) and the specificity of personalized one-to-one language teaching in a tutorial. The thesis stated by the author claims that tutorial, due to its different type of teacher-student interaction, varying epistemological background and distinctive levels of interactive rhetoric (e.g. its less instructional and more natural character) is not an obvious space for developing language competence. On the other hand, it may, as the space for very individual and intense learning context, promote development of communicative skills and critical thinking, thus helping to meet cognitive aims of the curriculum in philological studies at the university.